(untitled) (Journal of Namibian Studies : History Politics Culture, 2015)
Throughout the Global South, especially in Africa, young people are recognised as the future. At the same time, though, they are often prevented from assuming their rightful role in society. This is also true for Namibia and this concluding essay examines the plight of Namibia’s next generation.